Каґура - Наґамацу Ацусі (Народна творчість та етнографія, 2009)
The history of origin of Japanese kagura (from Japanese «music of deities»), folk theatrical art which is based on the recreation of the content of the old Japanese myths about the deity’s coming to the earth is covered in the article. The typology of folk kagura is offered and its varieties are analyzed:miko-kagura, torimono-kagura, yudate-kagura, shishi-kagura. Stage actions, incorporated under the name of kagura, in particular of Kyushu Island, Miyadzaki are described.